EVALUATION OF MOBILE APPLICATION FOR ANTICOAGULANT DRUG MANAGEMENT: IOS AND ANDROID PLATFORM - Alimuddin Alimuddin (Universitas Muhammadiyah Sorong, 2020)
Our goal was to identify the practical usage of medication management apps and what they can offer a consumer especially in their old age, keeping in view the aspect of medication adherence.A search of FREE medication management apps was conducted on app store of iPhone/Android operating system. Apps were included if they had a medication management system which included a reminder setup option and had an easy to use interface.Of the 22 apps on IOS and 18 apps on Android identified by strategy all met the inclusion criteria. WebMD and Drugs.com rated the highest among the apps because of their basic medication reminder feature coupled with their enhanced levels of functionality. WebMD was rated best for its information and usability which included a symptom checker, medication reminder, list of disease conditions, drug list with Indications, dosage information, side effects, drug interactions, drug use in pregnancy and lactation, first aid information, local health facilities listings, tests and procedures listings, healthy living tips, food and recipes.Finding a medication management app is challenging if you are looking for a specific type of apps as most of the apps are not tested by any authorized drug regulatory authority for example FDA. Almost all have no reviews and are not affiliated to any healthcare organization. Despite being untested, medication apps represent a possible strategy that pharmacists, healthcare workers, carers and family members of elderly patients can recommend for helping nonadherent patients and incorporate into their practice.Â